Code-Switching Practices in English Language Classrooms: A Classroom Discourse Analysis and Its Pedagogical Implications for EFL Learning - Rusdiana Junaid; Rustan Santaria; Masruddin; Nur Qalbi Rustan (Universitas Islam Negeri Palopo, 2025)
This study investigates code-switching practices in an Indonesian English as a Foreign Language (EFL) classroom through a qualitative classroom discourse analysis. Drawing on audio- and video-recorded classroom interaction, the study examines how teachers and students employ code-switching, the pedagogical functions it serves, and its implications for effective EFL teaching. The findings reveal that code-switching is systematic and predominantly teacher-initiated, occurring most frequently during instructional clarification, classroom management, and affective support. Student-initiated code-switching, although less frequent, functions primarily as an interactional repair strategy to maintain participation and negotiate meaning. Importantly, strategically timed code-switching mediates key learning processes, including comprehension facilitation, engagement regulation, and participation expansion. The study contributes empirical discourse-based evidence to ongoing debates on L1 use in EFL classrooms, challenging deficit-oriented perspectives and highlighting code-switching as a context-sensitive pedagogical resource. Implications are discussed for EFL pedagogy and teacher education in multilingual instructional settings.